Studies of advanced glycation end products and oxidation biomarkers for type 2 diabetes. (2nd May 2018) - Chiu, Chung‐Jung; Rabbani, Naila; Rowan, Sheldon; Chang, Min‐Lee; Sawyer, Sherilyn; Hu, Frank B.; Willett, Walter; Thornalley, Paul J.; Anwar, Attia; Bar, Liliana; Kang, Jae H.; Taylor, Allen
Abstract: Advanced glycation end products (AGEs ) are formed upon nonenzymatic reactions of sugars or their metabolites with proteins and other cellular constituents. Many AGEs are long lived. Recent findings suggest that AGEs may predict diabetes and its complications and thus may warrant further study. The objective of this study was to assess the validity of our experimental procedures for measuring AGEs in stored blood sample and to conduct a pilot study for developing AGE biomarkers for diabetes and/or age‐related changes of glucose metabolism. We conducted a reliability study of the samples and methods using liquid chromatography–tandem mass spectrometry (LC‐MS)/MS assays for 10 AGEs (including methylglyoxal‐derived hydroimidazolone (MG‐H1 ), glucosepane (GSP ) and two oxidation measures, in stored repository blood samples from the Nurses' Health Study and the Health Professionals Follow‐up Study. We also analyzed data relating blood GSP levels to type 2 diabetes status in a case‐control study (25 cases and 15 controls). Among the AGEs, GSP, and MG‐H1 showed the highest reliability across the various measures: reliability in duplicate samples and stability with delayed processing and storage over 1–2 year period. Furthermore, plasma GSP was associated with older age ( P = 0.04) and type 2 diabetes status (age‐adjusted P = 0.0475). Our findings suggest that analysis of these AGEs may be developed as biomarkers for diabetes and/or age‐related changes of glucose metabolism. © 2018 BioFactors, 44(3):281–288, 2018